2010
DOI: 10.1121/1.3294493
|View full text |Cite
|
Sign up to set email alerts
|

Application of the coherent-to-incoherent intensity ratio to estimation of ocean surface roughness from high-frequency, shallow-water propagation measurements

Abstract: For acoustic propagation through a shallow ocean channel or waveguide, the coherence between different transmissions is controlled primarily by the roughness of the ocean surface and to a lesser degree by fluctuations in the volume. In this study, the coherent-to-incoherent intensity ratio (CTIR) is defined as a way to quantify the coherence between multipath transmissions and ocean surface rms wave height and wind speed. A theory that connects the CTIR and the coherent surface reflection coefficient is develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…For a communications receiver, it is particularly challenging to harvest the energy from a diffuse tail. Long equalizers are required, and the problem is aggravated in waveguides with multiple surface interactions, as Doppler spread may then increase, and coherence may decrease with delay [16], [17], [26], [52]. Some incoherently scattered paths may still be useful for coherent communications [82], but there will be remaining signal energy that acts as noise with practical communication systems.…”
Section: Reverberationmentioning
confidence: 99%
See 1 more Smart Citation
“…For a communications receiver, it is particularly challenging to harvest the energy from a diffuse tail. Long equalizers are required, and the problem is aggravated in waveguides with multiple surface interactions, as Doppler spread may then increase, and coherence may decrease with delay [16], [17], [26], [52]. Some incoherently scattered paths may still be useful for coherent communications [82], but there will be remaining signal energy that acts as noise with practical communication systems.…”
Section: Reverberationmentioning
confidence: 99%
“…1). Surface gravity waves have a strong effect on signal propagation [12], [42], [45], [49]- [52], including time-varying path lengths [15], [41], [44], [53]- [55] and corresponding frequency shifts [51], [56], [57]. Even hydrodynamically calm surfaces are important scatterers of acoustic energy at high frequencies [45].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Ambient seismic noise is a ubiquitous signal that is recorded worldwide at seismic stations. At periods between 5 and 30 s, it is excited by the interaction between the ocean and the crust [e.g., Longuet-Higgins, 1950;Hasselmann, 1963;Tanimoto et al, 1998;Romanowicz, 2004, 2006;Shapiro et al, 2006;Kedar et al, 2008;Tanimoto, 2007;Zheng et al, 2008;Nishida et al, 2009;Roux et al, 2010;Ardhuin et al, 2011]. At short periods, Longuet-Higgins [1950] suggested that the interaction of the oceanic waves with the shallow seafloor forms the first microseism peak (10-20 s) and that the interference of those waves with their coastal reflection forms the second microseism peak (5-10 s).…”
Section: Introductionmentioning
confidence: 99%
“…5, the parameters R 12 , R 13 , and z are displayed. Consequently, based on Snell's law, R 12 and R 23 can be calculated using (20) where g 2 and g 3 are defined as follows: …”
Section: Bubbles Modelingmentioning
confidence: 99%
“…In most of these subjects, it is necessary to provide an appropriate acoustic model in order to entail sea surface effects on the entry sound. Active control and acoustic response of structure and fluid interaction [9,10], attenuation and absorption [11], bubble plumes [12][13][14][15], sound transmission [16][17][18], sound propagation in shallow water [19][20][21] and surface waves [22][23] can be considered as important phenomena in the sea.There are different approaches adopted by investigators in order to examine sound scattering from the sea surface. These approaches can be categorized as experimental, theoretical, and numerical studies [24].…”
mentioning
confidence: 99%